A light-weight carbon fiber bathtub and a method for manufacturing the same
Patent Information
- Application Number
- CN202611056490.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-20
AI Technical Summary
在单一涂层中同时实现高透明性、高硬度和足够韧性存在材料本身的理论矛盾,仅靠涂层材料配方的调整难以兼顾
1.本发明提供的轻量化碳纤维浴缸,通过在透明胶衣层中引入自制珠光填料,有效提升了表面抗划伤能力。该珠光填料以片状绢云母粉为基体,表面包覆由氢氧化铝煅烧转化而来的氧化铝纳米晶膜层,氧化铝本身具有高于树脂基体的硬度,以片状形态分散于胶衣层中,能分担外力作用时的接触应力,减少树脂基体直接受压产生的微凹陷变形,从而抑制微裂纹萌生和扩展。同时,填料表面经甲基三乙氧基硅烷与苯基三甲氧基硅烷水解缩合接枝了聚硅氧烷分子层,改善了填料与基础树脂体系的相容性,使其在胶衣中均匀分散,避免因团聚造成的局部缺陷,进一步保证了胶衣层硬度的均匀分布。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of bathroom fixtures technology, specifically relating to a lightweight carbon fiber bathtub and its preparation method. Background Technology
[0002] As a core fixture in the bathroom, the choice of materials for bathtubs directly affects their lifespan, user experience, and aesthetic appeal. Common bathtub materials on the market include acrylic, cast iron enamel, steel enamel, artificial stone, and fiberglass reinforced plastic. Carbon fiber composites, due to their high specific strength and modulus, corrosion resistance, and fatigue resistance, have been increasingly adopted in bathroom fixture manufacturing in recent years. A typical carbon fiber bathtub structure involves spraying gel coat resin onto a mold surface, then layering carbon fiber fabric and impregnating it with resin, followed by curing, demolding, trimming, polishing, and surface varnishing. Compared to acrylic bathtubs, carbon fiber bathtubs offer higher structural rigidity at the same wall thickness, allowing for thinner walls while maintaining sufficient load-bearing capacity and deformation resistance, thus achieving a degree of weight reduction.
[0003] However, in actual development and application, carbon fiber bathtubs face a difficult trade-off between lightweighting, surface hardness, and aesthetic quality. One key challenge is the conflict between lightweighting and surface hardness. To further reduce weight, some manufacturers have attempted to introduce lightweight sandwich structures. For example, Kohler uses a composite material structure with a foam core layer in some of its high-end bathtub product lines, using medium-density polyurethane foam or polyvinyl chloride foam as the core material and fiber-reinforced resin skins on both the top and bottom. While this type of sandwich structure reduces areal density, the compressive modulus of the foam core material is much lower than that of a solid composite layer. When external force is applied to the surface, the surface resin is prone to localized micro-deformation, causing the surface gel coat or varnish layer to bear greater bending stress, resulting in micro-cracks even at relatively low force levels. Under repeated micro-deformation and stress, these micro-cracks gradually expand, forming visible, shallow white marks. While the sandwich structure reduces weight, it comes at the cost of sacrificing surface scratch resistance.
[0004] Secondly, there is a need to mitigate the noise from water flow impact. When the bathtub wall thickness is reduced to 3 to 5 millimeters due to lightweight design, the water flow from the faucet impacts the bottom of the tub, exciting perceptible structural vibrations in the tub wall. These vibrations occur at frequencies roughly between 150 Hz and 700 Hz, falling within the low-to-mid frequency range where the human ear is most sensitive, resulting in a hollow or thin auditory experience. Consumers often associate this sound with negative perceptions such as low product quality and insufficient materials. Current technology commonly uses asphalt-based or butyl rubber damping sheets to suppress this vibration noise. However, these external damping materials have limited long-term resistance to humid heat aging and are prone to peeling off from the tub body in the long-term humid and hot environment of a bathroom, and also require additional manual processing.
[0005] Thirdly, there's the visual appeal of the carbon fiber woven texture. While the black woven texture of a carbon fiber bathtub certainly has a technological feel, the overall visual impression is rather dull. If only a simple transparent varnish layer is applied, its 60-degree gloss level typically only reaches 75 GU to 82 GU, resulting in a rather bland overall texture. If a high-crosslink density hard varnish is used to improve surface hardness and wear resistance, the varnish layer's transparency often decreases slightly due to the increased crosslink density, reducing light transmittance and obscuring the layered texture of the underlying carbon fiber woven texture, resulting in a dull and dark appearance. Achieving high transparency, high hardness, and sufficient toughness simultaneously in a single coating presents a theoretical contradiction inherent in the material itself, which is difficult to achieve by simply adjusting the coating material formulation.
[0006] In summary, no existing technology has yet found a carbon fiber bathtub solution that can effectively achieve synergy between lightweight design, surface hardness, vibration and noise reduction, and aesthetics. How to achieve a carbon fiber bathtub with low weight, high surface scratch resistance, robust sound feedback, and a glossy, layered appearance through integrated material and structural design is a technical problem to be solved in this field.
[0007] Therefore, there is a need to design a lightweight carbon fiber bathtub and its preparation method. Summary of the Invention
[0008] To overcome the shortcomings of existing technologies, a lightweight carbon fiber bathtub and its preparation method are provided.
[0009] To achieve the above objectives, the present invention provides the following technical solution: A lightweight carbon fiber bathtub, comprising, from the outside to the inside, a transparent gel coat layer, an outer surface reinforcement layer, a microsphere-filled core layer, and an inner structural layer; The transparent gel coat layer is formed by coating and curing a base resin system with added pearlescent fillers. The outer surface reinforcement layer is formed by curing carbon fiber twill fabric impregnated with the base resin system; The microsphere-filled core layer is formed by mixing hydroxyl-terminated polyurethane prepolymer, a base resin system and modified hollow glass microspheres, then coating and curing the mixture. The modified hollow glass microspheres are hollow glass microspheres whose surfaces have been treated with nano-silica deposition and epoxy-functionalized silane coupling agent. The inner structural layer is formed by curing carbon fiber twill fabric impregnated with the base resin system.
[0010] A method for preparing a lightweight carbon fiber bathtub includes the following steps: after coating a release agent onto the working surface of a bathtub mold, a layer of transparent gel coat resin system is coated, the transparent gel coat resin system comprising a base resin system and pearlescent filler, with a thickness of 0.12 mm to 0.25 mm, and gelled at room temperature until non-sticky; two layers of carbon fiber twill fabric are laid on the gel coat layer, and the base resin system is brushed or poured onto the fabric to impregnate it, forming an outer surface reinforcement layer; a core layer slurry is scraped onto the outer surface reinforcement layer, the core layer slurry being made of a mixture of hydroxyl-terminated polyurethane prepolymer, a base resin system, and modified hollow glass microspheres, with a scraping thickness of 0.8 mm to 2.5 mm; three layers of carbon fiber twill fabric are laid on the core layer slurry, and the base resin system is brushed or poured onto the fabric to impregnate it, forming an inner structural layer; then a release film, a breathable felt, and a vacuum bag film are sequentially covered, sealed, and vacuum cured, cooled in an oven to below 55°C for demolding, and then the surface is polished to obtain the finished bathtub.
[0011] The specific steps of the vacuum curing are as follows: evacuate to below -0.090 MPa, raise the temperature from room temperature to 80°C to 90°C at a rate of 0.8°C / min to 1.5°C / min, hold for 1.5 hours to 2 hours, continue to raise the temperature to 120°C to 140°C, and hold for 2.5 hours to 3.5 hours.
[0012] The basic resin system comprises a uniform mixture of bisphenol A type epoxy resin, methyl hexahydrophthalic anhydride, and 2,4,6-tris(dimethylaminomethyl)phenol, wherein the mass ratio of bisphenol A type epoxy resin to methyl hexahydrophthalic anhydride is 100:82 to 100:88, and the amount of 2,4,6-tris(dimethylaminomethyl)phenol added is 0.5% to 1.5% of the mass of bisphenol A type epoxy resin.
[0013] The carbon fiber twill fabric is a 3K carbon fiber twill fabric with a basis weight of 200 gsm to 240 gsm and a single layer thickness of 0.25 mm to 0.35 mm.
[0014] The preparation of the core layer slurry includes the following steps: adding modified hollow glass microspheres to a hydroxyl-terminated polyurethane prepolymer, then adding a basic resin system, stirring and mixing evenly and degassing to obtain the core layer slurry; the amount of the basic resin system added is 30% to 80% of the mass of the hydroxyl-terminated polyurethane prepolymer; The modified hollow glass microspheres are added at an amount of 20% to 48% of the mass of the hydroxyl-terminated polyurethane prepolymer; the mixing is carried out in a planetary stirrer at a speed of 200 rpm to 500 rpm for a time of 20 to 40 minutes; the degassing is carried out under a vacuum of -0.085 MPa for a time of 10 to 20 minutes.
[0015] The preparation method of the hydroxyl-terminated polyurethane prepolymer includes the following steps: Poly(1,4-butanediol adipate) diol with a number-average molecular weight of 1800 to 3200 and isophorone diisocyanate are added to a reactor at a molar ratio of NCO to OH of 0.65:1 to 0.85:1; dibutyltin dilaurate is added as a catalyst, the amount of which is 0.01% to 0.03% of the total material mass; the poly(1,4-butanediol adipate) diol is vacuum dehydrated at 100°C to 120°C until the water content is below 0.05% before being added; the reaction is carried out under nitrogen protection; the reaction is carried out at 70°C to 80°C for 1.5 to 2.5 hours; the NCO content is monitored until the detection value reaches zero, and the reaction is terminated to obtain a hydroxyl-terminated polyurethane prepolymer with a hydroxyl value of 35 mgKOH / g to 65 mgKOH / g.
[0016] In practical use of carbon fiber bathtubs, it was found that when the wall thickness is compressed to a thinner range due to lightweight requirements, the water flow from the faucet impacting the bottom of the tub excites the tub wall to bend and vibrate. The vibration frequency is concentrated in the low to mid-frequency range, which is perceived by the human ear as a hollow or thin sound. The current approach is to attach damping sheets to the outer bottom surface of the bathtub, but the external material is prone to peeling off in humid and hot environments, failing to solve the vibration problem at the structural level.
[0017] This invention incorporates a microsphere-filled core layer within the bathtub's layered structure. The core layer is formed by curing a mixture of hydroxyl-terminated polyurethane prepolymer, a base resin system, and modified hollow glass microspheres. The hydroxyl-terminated polyurethane prepolymer uses poly(1,4-butanediol adipate) and isophorone diisocyanate as raw materials. By controlling the molar ratio of NCO to OH to ensure an excess of OH, a linear prepolymer with hydroxyl groups at both ends of the molecular chain is obtained. Its main chain contains a large number of ester groups and flexible methylene segments. From a polymer physics perspective, the glass transition temperature of the soft segment of polyester polyurethane is typically below room temperature, placing it in a highly elastic state within the bathtub's operating temperature range, exhibiting strong chain mobility. When the tub wall is subjected to bending vibrations due to water flow, the vibration acts on the core layer as alternating stress. The polyurethane chains subsequently undergo conformational adjustments, and the internal friction between the chains converts mechanical energy into heat energy, which is dissipated, thus rapidly decaying the vibration. This damping behavior, based on the viscoelastic relaxation of the molecular chains, has an energy dissipation efficiency dependent on the degree of matching between the chain segment motion and the external force frequency.
[0018] In this scheme, the molecular weight of poly(1,4-butanediol adipate) is selected to be between 1800 and 3200. Its soft segment length is moderate, and its glass transition temperature is approximately -55°C to -60°C. At room temperature, it is in a highly elastic state with strong chain segment mobility, which is beneficial for viscoelastic dissipation of vibrational energy. During curing, the terminal hydroxyl groups of the polyurethane prepolymer undergo a ring-opening esterification reaction with methylhexahydrophthalic anhydride in the base resin system. After the anhydride ring is opened, the resulting carboxyl group undergoes addition esterification with the epoxy group, regenerating secondary hydroxyl groups. The newly generated hydroxyl groups can continue to open the next anhydride ring, thus repeating chain growth. The polyurethane segments are embedded in the epoxy-anhydride crosslinking network through covalent ester bonds, forming an epoxy-polyurethane interpenetrating network structure. The significance of this chemical bonding is that when vibrational stress is transmitted from the rigid epoxy network to the flexible polyurethane segments, the covalent ester bonds act as a channel for stress transmission, eliminating stress reflection barriers at the two-phase interface and avoiding the reduced energy dissipation efficiency caused by interfacial slip, which is common in physical blending systems. The polyurethane segments retain sufficient conformational freedom between crosslinking points to perform their damping function, while the crosslinking points prevent permanent slippage and fatigue accumulation of the segments under repeated deformation.
[0019] The preparation method of the modified hollow glass microspheres includes the following steps: preparing microspheres with a particle size distribution of 15 to 45 micrometers and a true density of 0.15 g / cm³. 3 Up to 0.30 g / cm 3Hollow glass microspheres were immersed in a 4% to 8% sodium hydroxide aqueous solution at 35°C to 50°C for 20 to 40 minutes, then washed and dried. Next, they were immersed in an ethanol-water solution containing tetraethyl orthosilicate, wherein the volume ratio of ethanol to water was 95:5, and the concentration of tetraethyl orthosilicate was 0.05 mol / L to 0.12 mol / L. The pH was adjusted to 9 to 10 with ammonia, and the mixture was stirred at 35°C to 45°C for 4 to 8 hours. The tetraethyl orthosilicate hydrolyzed and condensed to form nano-silica, which was deposited on the surface of the hollow glass microspheres, forming a layer with a thickness of 20 nm to 80 nm. A nano-silica deposition layer of nm was obtained, filtered, and dried at 110°C to 130°C for 30 to 60 minutes. Then, it was immersed in an ethanol-water solution containing γ-glycidoxypropyltrimethoxysilane, wherein the volume ratio of ethanol to water was 95:5, and the mass concentration of γ-glycidoxypropyltrimethoxysilane was 1.0% to 2.5%, and soaked at room temperature for 40 to 80 minutes. After removal, it was heat-treated at 90°C to 110°C for 1.5 to 3 hours to obtain modified hollow glass microspheres.
[0020] After addressing vibration damping, a trade-off exists between lightweighting and maintaining stiffness in the core layer. If a solid core layer is constructed solely from polyurethane prepolymer and a base resin system, its density approaches that of pure polymers, limiting the weight reduction effect. Furthermore, a pure polymer core layer exhibits a low compressive modulus under localized compression in the thickness direction, making it prone to micro-indentation deformation. Hollow glass microspheres, with their closed-cavity structure and true density of only 0.15 g / cm³ to 0.30 g / cm³, offer a direct means of reducing density when introduced into the core layer. However, commercially available hollow glass microspheres primarily have smooth borosilicate glass surfaces with limited silanol density. Their interfacial bonding with the organic resin matrix relies mainly on weak van der Waals forces and mechanical interlocking. Under stress, debonding easily occurs between the microspheres and the matrix. Once debonding forms voids, these voids expand into cracks under alternating stress, ultimately reducing the overall mechanical properties of the core layer.
[0021] Therefore, this invention performs multi-step surface modification on hollow glass microspheres. The first step involves treating the microspheres with a dilute sodium hydroxide aqueous solution at 35°C to 50°C, activating the glass surface through hydroxylation under relatively mild conditions. The silica-oxygen network on the glass surface partially hydrolyzes under alkaline conditions, exposing more silanol groups, which serve as anchor points for subsequent surface construction.
[0022] The second step uses tetraethyl orthosilicate as the silicon source, and a sol-gel process occurs under ammonia catalysis. The silicic acid produced by the hydrolysis of tetraethyl orthosilicate condenses and grows on the surface of the microspheres, forming a rough nano-silica layer with a thickness controlled between 20 nm and 80 nm. This rough layer increases the specific surface area of the microspheres, and the nanoscale uneven morphology provides mechanical intercalation sites for the resin. The newly formed silica layer contains a high density of silanol groups, providing abundant reaction sites for the subsequent grafting of silane coupling agents.
[0023] The third step involves surface modification using γ-glycidoxypropyltrimethoxysilane. The silanol groups at one end of the silane molecule hydrolyze and condense with the silanol groups on the microsphere surface to form Si-O-Si covalent bonds, while the epoxy groups at the other end remain exposed. During the subsequent high-temperature curing stage of the core layer, the epoxy groups on the microsphere surface participate in the ring-opening crosslinking reaction of the epoxy-anhydride in the base resin system, and the microspheres are covalently incorporated into the entire crosslinking network.
[0024] When the filler and matrix are chemically bonded, external forces can be effectively transferred to the filler particles through the interface layer, and the filler participates in load-bearing. In the core layer, the modified microspheres are no longer merely lightweight fillers occupying space, but become part of the cross-linked network, increasing the compressive modulus of the core layer while reducing overall density. The amount of the base resin system added to the core layer slurry is 30% to 80% of the prepolymer mass. This proportion ensures that a sufficient number of epoxy-anhydride cross-linking points are distributed throughout the core layer, enabling effective network connections to form between the epoxy groups on the microsphere surface and the matrix, as well as between microspheres themselves. Therefore, the modified hollow glass microspheres possess both weight reduction and reinforcement functions, ensuring that vibration damping is not sacrificed for overall stiffness despite the weight reduction.
[0025] The amount of pearlescent filler added is 4% to 12% of the mass of bisphenol A epoxy resin in the base resin system.
[0026] The preparation method of the pearlescent filler includes the following steps: dispersing flaky sericite powder with an aspect ratio of not less than 40 and a particle size of 5 to 25 micrometers in water to prepare an aqueous suspension with a mass concentration of 15% to 25%; adding aluminum chloride solution to the aqueous suspension to make the aluminum ion concentration 0.10 mol / L to 0.25 mol / L. Ammonia solution was added dropwise at 60°C to 80°C with stirring to adjust the pH to 5.5 to 6.5. The reaction was continued for 1 to 2 hours with stirring, followed by filtration and washing. The mixture was then calcined at 800°C to 950°C for 1.5 to 3 hours to obtain alumina-coated mica composite powder. The alumina-coated mica composite powder was ultrasonically dispersed in toluene, and a mixed silane with a mass ratio of methyltriethoxysilane to phenyltrimethoxysilane of 2:1 to 3:1 was added. The total amount of mixed silane added was 5% to 12% of the mass of the alumina-coated mica composite powder. The mixture was reacted at 75°C to 90°C under a nitrogen atmosphere for 6 to 9 hours, followed by washing and drying to obtain pearlescent filler.
[0027] Carbon fiber bathtubs also face the challenge of surface scratch resistance in practical use. The outer surface of carbon fiber composite products typically relies on a clear varnish layer to provide hardness and gloss, but there is an inherent contradiction between hardness and toughness in clear varnish. Increasing the crosslinking density to improve hardness leads to increased brittleness of the varnish layer, decreased transparency due to increased internal microgels, poorer uniformity of refractive index, and increased light scattering, ultimately causing the varnish layer to become hazy and obscuring the woven texture of the underlying carbon fibers.
[0028] This invention does not add a hard coating to the cured bathtub surface, but instead introduces a self-made pearlescent filler into the transparent gel coat layer for integrated curing. The pearlescent filler is prepared using flake-shaped sericite powder as the matrix. First, aluminum hydroxide colloid is deposited on the mica flake surface via liquid phase deposition. During deposition, aluminum ions hydrolyze to form aluminum hydroxide in a weakly acidic environment controlled by ammonia. The newly generated aluminum hydroxide colloid particles preferentially nucleate and grow heterogeneously on the mica flake surface, gradually forming a continuous coating layer. Subsequently, high-temperature calcination at 800℃ to 950℃ dehydrates and transforms the aluminum hydroxide into an α-alumina nanocrystalline film layer. The Mohs hardness of alumina is approximately 9, while that of cured epoxy resin is only 2 to 3. The alumina coating layer makes the overall hardness of the filler much higher than that of the resin matrix. When this filler is dispersed in the gel coat, the sheet-like filler covers a large area of the resin surface with its large diameter-to-thickness ratio when a hard object passes over the surface, thus sharing the external load and dispersing the compressive stress into a larger resin volume. This reduces the peak stress locally borne by the resin matrix, thereby inhibiting the initiation of micro-dents and micro-cracks.
[0029] Regarding transparency, the surface of the alumina-coated mica composite powder is further grafted with a mixed silane of methyltriethoxysilane and phenyltrimethoxysilane. After hydrolysis and condensation, the silane forms a polysiloxane molecular layer on the powder surface. Methyltriethoxysilane provides flexible siloxane segments, while phenyltrimethoxysilane introduces an aromatic ring structure. The combination of these two silanes makes the interfacial refractive index transition between the filler and bisphenol A epoxy resin smoother. The refractive index of bisphenol A epoxy resin is typically around 1.57 to 1.59, that of silica is approximately 1.46, that of alumina is approximately 1.76, and that of mica is approximately 1.58. Without surface modification, there are multiple abrupt refractive index interfaces between the multilayer structure of the filler and the resin matrix. Incident light undergoes partial reflection and scattering at each interface when penetrating the gel coat, macroscopically resulting in decreased transparency. After surface grafting with polysiloxane, the siloxane layer, as a transition layer with a refractive index between inorganic fillers and organic resins, reduces the interfacial reflectivity, reduces light scattering loss, and allows the gel coat layer to maintain good transparency, so that the weave texture of the underlying carbon fiber fabric can be clearly presented.
[0030] During gelcoat coating and leveling, the sheet-like sericite filler tends to align parallel to the mold's working surface due to shear force and surface tension. The parallel-aligned transparent layers produce multiple specular reflections and thin-film interference on incident light. The difference in optical path between the reflected light from different layers creates interference colors, resulting in a pearlescent shimmering visual effect. The dark base of the carbon fiber woven texture absorbs a large amount of light that penetrates the gelcoat without being reflected, making the pearlescent reflection even more striking against the dark background, creating rich visual depth.
[0031] The aforementioned transparent gel coat layer, outer surface reinforcement layer, microsphere-filled core layer, and inner structural layer all use a base resin system as a continuous crosslinking matrix, achieving integrated co-curing under vacuum conditions through stepped temperature increases. In the base resin system, bisphenol A epoxy resin and methylhexahydrophthalic anhydride undergo a crosslinking reaction under the action of the accelerator 2,4,6-tris(dimethylaminomethyl)phenol. The tertiary amine group of the accelerator first initiates the ring-opening of the anhydride. When the gel coat layer gels to a non-sticky state at room temperature, the crosslinking reaction only proceeds to near the gel point. This stage corresponds to the B-stage intermediate state of the epoxy resin, where the system has just lost its macroscopic fluidity but is far from complete curing, retaining unreacted epoxy groups and active carboxyl / ester groups formed by the ring-opening of the anhydride.
[0032] After the outer surface reinforcing carbon fiber fabric is laid and impregnated with the base resin system, the gel coat layer is heated again during the high-temperature curing stage. This increases the activity of the molecular chain segments, and the residual active groups undergo condensation coupling with the base resin system of the outer reinforcing layer, forming a continuous chemical cross-linked network at the gel coat-outer reinforcing layer interface, rather than a physical adhesive interface. Similarly, chemical bonding is achieved between the outer reinforcing layer and the core layer, and between the core layer and the inner structural layer, through co-crosslinking of the base resin system. There are no longer material interfaces between the layers; instead, they are fused into a whole through a continuous covalent network. The integrated chemical cross-linked structure of this invention distributes shear stress to an interpenetrating region of a certain thickness on both sides of the interface. Within this region, the epoxy network and polyurethane segments interpenetrate, significantly improving the interlayer bonding strength and preventing delamination failure.
[0033] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. The lightweight carbon fiber bathtub provided by this invention effectively improves the surface scratch resistance by introducing a self-made pearlescent filler into the transparent gel coat layer. This pearlescent filler uses flaky sericite powder as a matrix, coated with an alumina nanocrystalline film layer derived from the calcination of aluminum hydroxide. Alumina itself has a higher hardness than the resin matrix and is dispersed in the gel coat layer in a flaky form, which can share the contact stress under external force, reducing micro-indentation deformation caused by direct pressure on the resin matrix, thereby inhibiting the initiation and propagation of microcracks. Simultaneously, the filler surface is grafted with a polysiloxane molecular layer through the hydrolysis and condensation of methyltriethoxysilane and phenyltrimethoxysilane, improving the compatibility between the filler and the base resin system, ensuring uniform dispersion in the gel coat, avoiding local defects caused by agglomeration, and further guaranteeing a uniform distribution of the gel coat layer's hardness.
[0034] 2. This invention places a microsphere-filled core layer between the outer surface reinforcement layer and the inner structural layer. The hydroxyl-terminated polyurethane prepolymer in the core layer contains a large number of flexible polyester segments. When subjected to cylinder wall bending vibration caused by water flow impact, these segments convert mechanical vibration energy into heat dissipation through intramolecular friction, accelerating the vibration decay rate and changing the perceived sound from hollow to muffled and solid. Simultaneously, the modified hollow glass microspheres dispersed in the core layer, treated with nano-silica deposition and epoxy-functionalized silane coupling agents, participate in the construction of the core layer's cross-linking network through chemical bonds. While maintaining the low density of the core layer, this enhances its compressive modulus and structural stability, ensuring that the vibration damping function does not sacrifice overall stiffness due to weight reduction.
[0035] 3. This invention utilizes the combination of pearlescent filler in a transparent gel coat layer and the woven texture of carbon fiber to give the bathtub surface a layered decorative effect. The flake-like alumina-coated mica matrix of the pearlescent filler is arranged approximately parallel to the surface within the transparent gel coat, producing multiple specular reflections and transmission interference on incident light, resulting in a pearlescent shimmering effect. The underlying woven texture of the carbon fiber twill fabric serves as a dark base, creating a contrast and visual depth with the pearlescent reflections, breaking the monotony and dullness of pure carbon fiber products. The presence of the polysiloxane molecular layer avoids interfacial light scattering caused by abrupt changes in refractive index between the filler and resin, ensuring the transparency of the gel coat layer and allowing the underlying carbon fiber texture to be clearly displayed.
[0036] 4. The transparent gel coat layer, outer surface reinforcement layer, microsphere-filled core layer, and inner structural layer of this invention all contain a basic resin system. During the curing process, this system simultaneously undergoes a ring-opening crosslinking reaction between epoxy groups and acid anhydrides, as well as an addition reaction between acid anhydrides and epoxy groups and the terminal hydroxyl groups of hydroxyl-terminated polyurethane prepolymers, forming a continuous crosslinked structure in which epoxy-acid anhydride networks and polyurethane segments interpenetrate. The epoxy functional groups on the surface of the modified hollow glass microspheres participate in this crosslinking process, fixing the hollow microspheres to the network with covalent bonds. This avoids the problem of interfacial debonding and delamination between different material layers in traditional sandwich structures due to physical adhesion alone, which occurs during long-term use or under alternating hot and cold conditions. This allows each functional layer to maintain its respective contribution while forming an overall load-bearing structure. Attached Figure Description
[0037] Figure 1 The results are from a surface gloss test at 60 degrees. Figure 2 The results are from the areal density test. Figure 3 The results are from the vibration decay time test. Figure 4 These are the results of the interlaminar shear strength test. Detailed Implementation
[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0039] In the specific embodiments of this application, the chemical reagents and raw materials used in the examples and comparative examples are all conventional commercially available products unless otherwise specified. The sources of various main raw materials are briefly described below: Bisphenol A type epoxy resin: purchased from Guangdong Shengke Biochemical Technology Co., Ltd., CAS No. 25085-99-8.
[0040] Methylhexahydrophthalic anhydride: purchased from Puyang Huicheng Electronic Materials Co., Ltd., CAS No. 25550-51-0.
[0041] 2,4,6-Tris(dimethylaminomethyl)phenol: Purchased from Huizhou Shengshida Technology Co., Ltd., this chemical is abbreviated as DMP-30, CAS number 90-72-2.
[0042] Poly(1,4-butanediol adipate) diol (PBA) was purchased from Wuhan Kemic Biomedical Technology Co., Ltd., CAS No. 150923-12-9.
[0043] Isophorone diisocyanate: purchased from Wanhua Chemical Group Co., Ltd., CAS No. 4098-71-9.
[0044] Dibutyltin dilaurate: CAS No. 77-58-7, purchased from Hubei Xinlantian New Materials Co., Ltd.
[0045] Tetraethyl orthosilicate: purchased from Shaoxing Zhonglei New Materials Co., Ltd., CAS No. 78-10-4.
[0046] γ-glycidyl etheroxypropyltrimethoxysilane: purchased from Nanjing Herun Coupling Agent Co., Ltd., CAS No. 2530-83-8, model KH-560.
[0047] Microcrystalline wax: purchased from Cangzhou Forest Wax Industry Co., Ltd.
[0048] Methyltriethoxysilane: purchased from Jiangxi Hongbai New Materials Co., Ltd., CAS No. 2031-67-6.
[0049] Phenylacetyltrimethoxysilane: purchased from Jiangxi Hongbai New Materials Co., Ltd., CAS No. 2996-92-1.
[0050] Sericite powder: purchased from Anhui Suxing Yonghe Powder Materials Technology Co., Ltd., and produced using a wet grinding and crushing process.
[0051] Hollow glass microspheres: purchased from Shanxi Hainuo Technology Co., Ltd.
[0052] Carbon fiber twill fabric: purchased from Zhongfu Shenying Carbon Fiber Co., Ltd.
[0053] The technical solution of this application is as follows: A lightweight carbon fiber bathtub, comprising, from the outside to the inside, a transparent gel coat layer, an outer surface reinforcement layer, a microsphere-filled core layer, and an inner structural layer; The transparent gel coat layer is formed by coating and curing a base resin system with added pearlescent fillers. The outer surface reinforcement layer is formed by curing carbon fiber twill fabric impregnated with the base resin system; The microsphere-filled core layer is formed by mixing hydroxyl-terminated polyurethane prepolymer, a base resin system and modified hollow glass microspheres, then coating and curing the mixture. The modified hollow glass microspheres are hollow glass microspheres whose surfaces have been treated with nano-silica deposition and epoxy-functionalized silane coupling agent. The inner structural layer is formed by curing carbon fiber twill fabric impregnated with the base resin system.
[0054] A method for preparing a lightweight carbon fiber bathtub includes the following steps: after coating a release agent onto the working surface of a bathtub mold, a layer of transparent gel coat resin system is coated, the transparent gel coat resin system comprising a base resin system and pearlescent filler, with a thickness of 0.12 mm to 0.25 mm, and gelled at room temperature until non-sticky; two layers of carbon fiber twill fabric are laid on the gel coat layer, and the base resin system is brushed or poured onto the fabric to impregnate it, forming an outer surface reinforcement layer; a core layer slurry is scraped onto the outer surface reinforcement layer, the core layer slurry being made of a mixture of hydroxyl-terminated polyurethane prepolymer, a base resin system, and modified hollow glass microspheres, with a scraping thickness of 0.8 mm to 2.5 mm; three layers of carbon fiber twill fabric are laid on the core layer slurry, and the base resin system is brushed or poured onto the fabric to impregnate it, forming an inner structural layer; then a release film, a breathable felt, and a vacuum bag film are sequentially covered, sealed, and vacuum cured, cooled in an oven to below 55°C for demolding, and then the surface is polished to obtain the finished bathtub.
[0055] The specific steps of the vacuum curing are as follows: evacuate to below -0.090 MPa, raise the temperature from room temperature to 80°C to 90°C at a rate of 0.8°C / min to 1.5°C / min, hold for 1.5 hours to 2 hours, continue to raise the temperature to 120°C to 140°C, and hold for 2.5 hours to 3.5 hours.
[0056] The basic resin system comprises a uniform mixture of bisphenol A type epoxy resin, methyl hexahydrophthalic anhydride, and 2,4,6-tris(dimethylaminomethyl)phenol, wherein the mass ratio of bisphenol A type epoxy resin to methyl hexahydrophthalic anhydride is 100:82 to 100:88, and the amount of 2,4,6-tris(dimethylaminomethyl)phenol added is 0.5% to 1.5% of the mass of bisphenol A type epoxy resin.
[0057] The amount of pearlescent filler added is 4% to 12% of the mass of bisphenol A epoxy resin in the base resin system.
[0058] The preparation method of the pearlescent filler includes the following steps: dispersing flaky sericite powder with an aspect ratio of not less than 40 and a particle size of 5 to 25 micrometers in water to prepare an aqueous suspension with a mass concentration of 15% to 25%; adding aluminum chloride solution to the aqueous suspension to make the aluminum ion concentration 0.10 mol / L to 0.25 mol / L. Ammonia solution was added dropwise at 60°C to 80°C with stirring to adjust the pH to 5.5 to 6.5. The reaction was continued for 1 to 2 hours with stirring, followed by filtration and washing. The mixture was then calcined at 800°C to 950°C for 1.5 to 3 hours to obtain alumina-coated mica composite powder. The alumina-coated mica composite powder was ultrasonically dispersed in toluene, and a mixed silane with a mass ratio of methyltriethoxysilane to phenyltrimethoxysilane of 2:1 to 3:1 was added. The total amount of mixed silane added was 5% to 12% of the mass of the alumina-coated mica composite powder. The mixture was reacted at 75°C to 90°C under a nitrogen atmosphere for 6 to 9 hours, followed by washing and drying to obtain pearlescent filler.
[0059] The preparation of the core layer slurry includes the following steps: adding modified hollow glass microspheres to a hydroxyl-terminated polyurethane prepolymer, then adding a basic resin system, stirring and mixing evenly and degassing to obtain the core layer slurry; the amount of the basic resin system added is 30% to 80% of the mass of the hydroxyl-terminated polyurethane prepolymer; The modified hollow glass microspheres are added at an amount of 20% to 48% of the mass of the hydroxyl-terminated polyurethane prepolymer; the mixing is carried out in a planetary stirrer at a speed of 200 rpm to 500 rpm for a time of 20 to 40 minutes; the degassing is carried out under a vacuum of -0.085 MPa for a time of 10 to 20 minutes.
[0060] The preparation method of the modified hollow glass microspheres includes the following steps: preparing microspheres with a particle size distribution of 15 to 45 micrometers and a true density of 0.15 g / cm³. 3 Up to 0.30 g / cm 3Hollow glass microspheres were immersed in a 4% to 8% sodium hydroxide aqueous solution at 35°C to 50°C for 20 to 40 minutes, then washed and dried. Next, they were immersed in an ethanol-water solution containing tetraethyl orthosilicate, wherein the volume ratio of ethanol to water was 95:5, and the concentration of tetraethyl orthosilicate was 0.05 mol / L to 0.12 mol / L. The pH was adjusted to 9 to 10 with ammonia, and the mixture was stirred at 35°C to 45°C for 4 to 8 hours. The tetraethyl orthosilicate hydrolyzed and condensed to form nano-silica, which was deposited on the surface of the hollow glass microspheres, forming a layer with a thickness of 20 nm to 80 nm. A nano-silica deposition layer of nm was obtained, filtered, and dried at 110°C to 130°C for 30 to 60 minutes. Then, it was immersed in an ethanol-water solution containing γ-glycidoxypropyltrimethoxysilane, wherein the volume ratio of ethanol to water was 95:5, and the mass concentration of γ-glycidoxypropyltrimethoxysilane was 1.0% to 2.5%, and soaked at room temperature for 40 to 80 minutes. After removal, it was heat-treated at 90°C to 110°C for 1.5 to 3 hours to obtain modified hollow glass microspheres.
[0061] The preparation method of the hydroxyl-terminated polyurethane prepolymer includes the following steps: Poly(1,4-butanediol adipate) diol with a number-average molecular weight of 1800 to 3200 and isophorone diisocyanate are added to a reactor at a molar ratio of NCO to OH of 0.65:1 to 0.85:1; dibutyltin dilaurate is added as a catalyst, the amount of which is 0.01% to 0.03% of the total material mass; the poly(1,4-butanediol adipate) diol is vacuum dehydrated at 100°C to 120°C until the water content is below 0.05% before being added; the reaction is carried out under nitrogen protection; the reaction is carried out at 70°C to 80°C for 1.5 to 2.5 hours; the NCO content is monitored until the detection value reaches zero, and the reaction is terminated to obtain a hydroxyl-terminated polyurethane prepolymer with a hydroxyl value of 35 mgKOH / g to 65 mgKOH / g.
[0062] The carbon fiber twill fabric is a 3K carbon fiber twill fabric with a basis weight of 200 gsm to 240 gsm and a single layer thickness of 0.25 mm to 0.35 mm.
[0063] The present invention will be described in detail below with reference to examples and comparative examples, but the scope of protection of the present invention is not limited to these examples.
[0064] Example 1 Preparation of hydroxyl-terminated polyurethane prepolymer: Poly(1,4-butanediol adipate) diol with a number average molecular weight of 1800 was vacuum dehydrated to a water content of 0.04% at 120℃. The diol and isophorone diisocyanate were added to a nitrogen-protected reactor at a molar ratio of NCO to OH of 0.75:1. Dibutyltin dilaurate was added at 0.01% of the total material mass. The reaction was carried out at 80℃ for 2.0 hours. The NCO content was monitored until it returned to zero, and a prepolymer with a hydroxyl value of 50 mg KOH / g was obtained.
[0065] Surface modification of hollow glass microspheres: Glass microspheres with a particle size of 45 μm and a true density of 0.22 g / cm³ were immersed in a 4% sodium hydroxide aqueous solution at 50°C for 30 minutes, then washed and dried. Next, they were immersed in an ethanol-water solution with a tetraethyl orthosilicate concentration of 0.12 mol / L (ethanol to water volume ratio 95:5), and the pH was adjusted to 9.0 with ammonia. The mixture was stirred at 45°C for 6 hours, during which tetraethyl orthosilicate hydrolyzed and condensed to form nano-silica, which was deposited on the surface of the microspheres, forming a deposition layer with a thickness of 80 nm. After filtration, the microspheres were dried at 110°C for 60 minutes. Finally, they were immersed in an ethanol-water solution containing 1.0% γ-glycidyl oxypropyltrimethoxysilane (ethanol to water volume ratio 95:5) at room temperature for 80 minutes. After removal, the microspheres were heat-treated at 90°C for 3.0 hours to obtain modified hollow glass microspheres.
[0066] Preparation of pearlescent filler: Flaky sericite powder with an aspect ratio of not less than 40 and a particle size of 5 μm was dispersed in water to prepare a suspension with a mass concentration of 25%. Aluminum chloride solution was added to achieve an aluminum ion concentration of 0.10 mol / L. Ammonia was added dropwise at 80℃ to adjust the pH to 5.5, and the reaction was continued for 2.0 hours. The mixture was then filtered and washed. The powder was calcined at 800℃ for 3.0 hours to obtain alumina-coated mica composite powder. This powder was ultrasonically dispersed in toluene, and a mixed silane of methyltriethoxysilane and phenyltrimethoxysilane in a mass ratio of 2:1 was added at 12% of the powder mass. The mixture was reacted at 75℃ under nitrogen for 9.0 hours, and then washed and dried to obtain the pearlescent filler.
[0067] Preparation of the base resin system: Bisphenol A type epoxy resin, methyl hexahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol are mixed evenly in a mass ratio of 100:88:1.5, and the amount of accelerator is 1.5% of the mass of epoxy resin.
[0068] Formulate the resin system for the gel coat layer: Add pearlescent filler at a mass of 12% of epoxy resin to the above-mentioned base resin system and mix thoroughly.
[0069] Preparation of core layer slurry: Add the above modified hollow glass microspheres at 20% of the mass of hydroxyl-terminated polyurethane prepolymer, and then add the base resin system at 80% of the mass of the prepolymer. Stir at 500 rpm for 20 minutes in a planetary stirrer, and then degas at -0.085 MPa for 20 minutes.
[0070] Lamination and Molding: After spraying a semi-permanent release agent onto the working surface of the steel bathtub mold, a gel coat layer resin system is sprayed on, with a gel coat layer thickness of 0.12mm, and gelled at room temperature until it is no longer sticky. Two layers of 3K carbon fiber twill fabric with a weight of 240gsm and a single layer thickness of 0.35mm are laid on. The base resin system is poured onto the fabric and impregnated with a roller brush to form an outer surface reinforcement layer. A core layer slurry is scraped onto the outer surface reinforcement layer with a thickness of 2.5mm. Three layers of the above-mentioned carbon fiber twill fabric are laid on the core layer slurry and impregnated with the base resin system to form an inner structural layer. A release film, a breathable felt, and a vacuum bag film are sequentially covered, sealed, and vacuumed to -0.095MPa. The temperature is raised from room temperature to 90℃ at a rate of 0.8℃ / min and held for 2.0 hours. The temperature is then raised to 120℃ and held for 3.5 hours. The bathtub is then cooled to below 55℃ in the furnace for demolding. The surface is polished with a wool wheel dipped in microcrystalline wax to obtain the finished bathtub.
[0071] Example 2 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: Preparation of hydroxyl-terminated polyurethane prepolymer: Poly(1,4-butanediol adipate) diol with a number average molecular weight of 3200 was vacuum dehydrated to a water content of 0.04% at 100℃. It was then added to a reactor with isophorone diisocyanate at a molar ratio of NCO to OH of 0.85:1. 0.02% of dibutyltin dilaurate was added to the reactor, and the reaction was carried out at 70℃ for 2.5 hours until the NCO content returned to zero, yielding a prepolymer with a hydroxyl value of 65 mg KOH / g.
[0072] Surface modification of hollow glass microspheres: Glass microspheres with a particle size of 15 μm and a true density of 0.30 g / cm³ were immersed in an 8% sodium hydroxide aqueous solution at 35°C for 40 minutes, then washed and dried. Next, they were immersed in an ethanol-water solution with a tetraethyl orthosilicate concentration of 0.05 mol / L, the pH was adjusted to 10, and the mixture was stirred at 35°C for 8.0 hours to generate a 20 nm thick nano-silica deposition layer. After filtration, the layer was dried at 130°C for 30 minutes. Finally, the microspheres were immersed in an ethanol-water solution containing 2.5% γ-glycidyl oxypropyltrimethoxysilane at 2.5% concentration for 40 minutes at room temperature. After removal, they were heat-treated at 110°C for 1.5 hours to obtain modified hollow glass microspheres.
[0073] Preparation of pearlescent filler: 25 μm flaky sericite powder was dispersed in water to prepare a 15% (w / w) suspension; aluminum chloride solution was added to make the aluminum ion concentration 0.25 mol / L; ammonia was added dropwise to adjust the pH to 6.5 while stirring at 60 °C; the reaction was continued for 1.0 hour, filtered and washed; calcined at 950 °C for 1.5 hours to obtain alumina-coated mica composite powder; the powder was ultrasonically dispersed in toluene; a mixed silane of methyltriethoxysilane and phenyltrimethoxysilane in a mass ratio of 3:1 was added at 5% of the powder mass; the reaction was carried out at 90 °C under nitrogen for 6.0 hours; and the powder was washed and dried to obtain the pearlescent filler.
[0074] Preparation of the basic resin system: Bisphenol A type epoxy resin, methyl hexahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol are mixed in a mass ratio of 100:82:0.5.
[0075] Formulating the gel coat resin system: Add pearlescent filler at 4% of the epoxy resin mass to the base resin system. Formulating the core layer slurry: Add modified hollow glass microspheres at 48% of the prepolymer mass, then add 30% of the prepolymer mass to the base resin system. Stir at 200 rpm for 40 minutes in a planetary stirrer, then degas at -0.090 MPa for 10 minutes.
[0076] Lamination and molding: Spray a gel coat layer with a thickness of 0.25mm, and after gelation, lay two layers of 3K carbon fiber twill fabric with a weight of 200gsm and a thickness of 0.25mm, and impregnate with a base resin system; scrape a core layer slurry with a thickness of 0.8mm; lay three layers of carbon fiber twill fabric, and impregnate with a base resin system; after sealing, evacuate to -0.092MPa, raise the temperature from room temperature to 80℃ at a rate of 1.5℃ / min, hold for 1.5 hours, then raise the temperature to 140℃ and hold for 2.5 hours, cool and demold with the furnace, and polish to obtain the finished bathtub.
[0077] Example 3 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: Preparation of hydroxyl-terminated polyurethane prepolymer: Poly(1,4-butanediol adipate) diol with a number average molecular weight of 2500 was dehydrated under vacuum at 110℃, fed at a molar ratio of NCO to OH of 0.65:1, and 0.03% catalyst was added. The reaction was carried out at 75℃ for 1.5 hours to obtain a prepolymer with a hydroxyl value of 35 mgKOH / g.
[0078] Surface modification of hollow glass microspheres: Glass microspheres with a particle size of 30 μm and a true density of 0.15 g / cm³ were immersed in a 6% sodium hydroxide aqueous solution at 42°C for 20 minutes, then washed and dried. Next, they were immersed in an ethanol-water solution with a tetraethyl orthosilicate concentration of 0.08 mol / L, the pH was adjusted to 9.5, and the mixture was stirred at 40°C for 4.0 hours to generate a 50 nm thick nano-silica deposition layer. After filtration, the layer was dried at 120°C for 45 minutes. Finally, the microspheres were immersed in an ethanol-water solution containing 1.8% γ-glycidoxypropyltrimethoxysilane at 1.8% concentration for 60 minutes at room temperature. After removal, the microspheres were heat-treated at 100°C for 2.0 hours to obtain the modified hollow glass microspheres.
[0079] Preparation of pearlescent filler: 15 μm flaky sericite powder was dispersed in water to prepare a 20% (w / w) suspension; aluminum chloride solution was added to make the aluminum ion concentration 0.17 mol / L; ammonia was added dropwise to adjust the pH to 6.0 while stirring at 70 °C; the reaction was continued for 1.5 hours, filtered and washed; calcined at 880 °C for 2.0 hours to obtain alumina-coated mica composite powder; the powder was ultrasonically dispersed in toluene; a mixed silane of methyltriethoxysilane and phenyltrimethoxysilane in a mass ratio of 2.5:1 was added, at an amount of 8% of the powder mass; the reaction was carried out at 82 °C under nitrogen for 7.5 hours; the powder was washed and dried to obtain the pearlescent filler.
[0080] Preparation of the base resin system: Bisphenol A type epoxy resin, methylhexahydrophthalic anhydride, and 2,4,6-tris(dimethylaminomethyl)phenol are mixed at a mass ratio of 100:85:1.0. Preparation of the gel coat layer resin system: Pearl filler, accounting for 8% of the epoxy resin mass, is added to the base resin system. Preparation of the core layer slurry: Modified hollow glass microspheres are added at 34% of the prepolymer mass, followed by 55% of the prepolymer mass to the base resin system. The mixture is stirred at 350 rpm for 30 minutes in a planetary stirrer, and then degassed at -0.088 MPa for 15 minutes.
[0081] Lamination and molding: Spray a gel coat layer with a thickness of 0.18 mm, and after gelation, lay two layers of 3K carbon fiber twill fabric with a weight of 220 gsm and a thickness of 0.30 mm, and impregnate with a base resin system; scrape a core layer slurry with a thickness of 1.6 mm; lay three layers of the above fabric and impregnate; after sealing, evacuate to -0.093 MPa, raise the temperature from room temperature to 85°C at a rate of 1.2°C / min, hold for 1.8 hours, raise the temperature to 130°C, hold for 3.0 hours, cool and demold with the furnace to obtain the finished bathtub.
[0082] Example 4 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: In the preparation of hydroxyl-terminated polyurethane prepolymer, the number-average molecular weight of poly(1,4-butanediol adipate) diol was 3000, the molar ratio of NCO to OH was 0.75:1, the amount of dibutyltin dilaurate catalyst was 0.02%, the dehydration temperature was 110℃, the reaction temperature was 75℃, the reaction time was 2.0 hours, and the hydroxyl value of the product was 50 mgKOH / g.
[0083] In the modification of hollow glass microspheres, the microspheres had a particle size of 30 μm and a true density of 0.22 g / cm³. The NaOH concentration was 6%, and the microspheres were soaked at 42℃ for 30 minutes. The tetraethyl orthosilicate concentration was 0.08 mol / L, the pH was 9.5, and the microspheres were reacted at 40℃ for 6.0 hours, resulting in a nano-silica layer thickness of 50 nm. The silane coupling agent concentration was 1.8%, and the microspheres were soaked at room temperature for 60 minutes and then heat-treated at 100℃ for 2.0 hours.
[0084] In the preparation of pearlescent filler, the sericite powder has a particle size of 15μm, a suspension concentration of 20%, an aluminum ion concentration of 0.17mol / L, and is reacted at 70℃ and pH 6.0 for 1.5 hours, followed by calcination at 880℃ for 2.0 hours; the mixed silane has a mass ratio of 2.5:1, an addition amount of 8%, and a reaction temperature of 82℃ for 7.5 hours.
[0085] In the basic resin system, the mass ratio of bisphenol A epoxy resin to methylhexahydrophthalic anhydride is 100:85, and the amount of accelerator is 1.0%.
[0086] The amount of pearlescent filler added to the gel coat layer is 8%. The amount of modified microspheres added to the core layer slurry is 34%, and the amount of basic resin system added is 55%. Stir at 350 rpm for 30 minutes, and degas at a vacuum degree of -0.088 MPa for 15 minutes.
[0087] The gel coat layer is 0.18 mm thick; the carbon fiber twill fabric has a weight of 220 gsm and a thickness of 0.30 mm; the core layer coating thickness is 1.6 mm; the vacuum curing heating rate is 1.2℃ / min, the first stage is kept at 85℃ for 1.8 hours, and the second stage is kept at 130℃ for 3.0 hours.
[0088] Comparative Example 1 In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows: No pearlescent fillers are added to the transparent gel coat layer; the base resin system is used directly as the gel coat layer.
[0089] Comparative Example 2 In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows: The core layer slurry does not contain modified hollow glass microspheres; it is composed solely of a mixture of hydroxyl-terminated polyurethane prepolymer and a base resin system.
[0090] Comparative Example 3 In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows: The core layer slurry does not contain a basic resin system; it consists only of a mixture of hydroxyl-terminated polyurethane prepolymer and modified hollow glass microspheres.
[0091] Comparative Example 4 In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows: Hollow glass microspheres were added directly to the core layer slurry in their original state without any surface modification treatment.
[0092] Comparative Example 5 In this comparative example, the similarities with Example 4 will not be repeated, and the differences are as follows: A single-layer solid carbon fiber epoxy bathtub is formed using a conventional hand lay-up process. The wall thickness is 3.5mm, there is no core layer, and the surface is sprayed with a two-component acrylic polyurethane varnish to achieve a gloss level similar to that of an epoxy bathtub.
[0093] Performance Test Results and Analysis The following test methods were used to evaluate the performance of the bathtubs manufactured in the embodiments and comparative examples. Surface pencil hardness was tested according to GB / T 6739, using a pencil hardness tester at five points on different areas of the bathtub's outer surface, and the lowest value was recorded. Surface 60-degree gloss was tested according to GB / T 9754, using six points on a flat area of the bathtub and the average value was recorded (gloss data was measured after polishing the surface with a wool wheel dipped in microcrystalline wax). Areal density was calculated by cutting 100mm × 100mm square samples, weighing them, and dividing the mass by the area. Sampling locations were two at each of the bottom, sidewall, and edge of the bathtub, and the average value was recorded. Vibration attenuation performance was tested using the hammer excitation method. The bathtub was placed upside down on a flexible support, and the bottom center was struck with a hammer. An accelerometer was used to pick up the vibration response, and the time required for the vibration amplitude to decrease by 20dB was taken as the vibration attenuation time. The test was repeated five times, and the average value was recorded. Interlaminar shear strength was tested according to GB / T 1450.1, using short beam samples cut from the flat area of the bathtub with a span-to-thickness ratio of 5:1 and a loading speed of 1.5mm / min. The heat resistance and humidity cycling performance test involved maintaining the sample at 85℃ and 85% relative humidity for 96 hours, then transferring it to -20℃ for 8 hours, repeating this cycle three times, and observing for cracks or delamination on the gel coat surface. The test results are detailed in Table 1 and the appendix. Figure 1-4 As shown.
[0094] It can be seen that Examples 1 to 4 exhibited good performance in pencil hardness, gloss, areal density, and vibration decay time, and remained intact after heat and humidity cycling. As shown in Table 1, the pencil hardness of the samples from Examples 1 to 4 reached 5H to 6H, which is a significant improvement compared to 3H in Comparative Examples 1 and 5. This is because a pearlescent filler containing an alumina nanocrystalline film was introduced into the transparent gel coat layer. The flake-shaped alumina-coated mica shared the external load, reducing the direct compressive deformation of the resin matrix. At the same time, the polysiloxane grafting treatment ensured uniform dispersion of the filler, avoiding stress concentration points.
[0095] Comparative Example 1, without the addition of pearlescent filler, has a gel coat hardness solely based on the hardness of the base resin system, resulting in a lower hardness. Comparative Example 5, employing a single-layer solid structure and relying solely on an external varnish coating, also exhibits limited surface hardness. The pencil hardness of Comparative Example 3 drops to 4H, lower than the 5H to 6H of the Examples and Comparative Example 4. This is likely because the gel coat layer thickness is only 0.12 mm to 0.25 mm, constituting a thin-film coating. Its apparent pencil hardness depends not only on the resin / filler composition of the gel coat itself but also significantly on the supporting stiffness of the underlying material. In Comparative Example 3, the core layer lacks the base resin system and the epoxy-anhydride highly cross-linked network, consisting only of flexible polyurethane segments and modified microspheres. The compressive modulus of the core layer is lower than that of the core layer in the Examples containing the epoxy-anhydride interpenetrating network, leading to slight elastic deformation of the underlying layer during pencil scratching. This increases the local bending stress of the gel coat layer, making scratches easier to form and reducing hardness.
[0096] like Figure 1 As shown, Example 4 achieved a 60-degree gloss of 91 GU, higher than Comparative Example 1's 83 GU and Comparative Example 5's 85 GU. Comparative Example 1, lacking pearlescent filler, had a transparent gelcoat but no multi-reflection brightening effect; the outer clear coat of Comparative Example 5 had a generally lower gloss. The lamellar structure of the pearlescent filler, arranged almost parallel within the gelcoat, produced specular reflection and interference of incident light, creating visual depth in conjunction with the underlying carbon fiber woven texture, thus enhancing the overall gloss and sense of layering.
[0097] Figure 2 The areal density data show that the areal density of the embodiments ranges from 2.8 to 3.6 kg·m³. -2 Between, compared to 5.4 kg·m in Comparative Example 5 -2 The density is significantly reduced, demonstrating the lightweight effect. The density of the modified hollow glass microspheres in the core layer is only 0.15 to 0.30 g·cm³. -3 Furthermore, its high volume fraction effectively reduced the overall areal density. Comparative Example 2, without microspheres, had a solid polyurethane-epoxy cured core, resulting in an areal density of 3.7 kg·m³. -2 This is higher than the 2.9 kg·m³ in Example 4. -2 This verifies the direct contribution of hollow microspheres to lightweighting.
[0098] Vibration decay time reflects the fullness of the sound after the bathtub is impacted, specifically as follows: Figure 3 As shown, the decay time of Example 4 was only 0.28 s, while that of Comparative Example 2 was 0.56 s and Comparative Example 5 was 0.87 s. This difference is mainly due to the change in energy dissipation within the core layer. In Example 4, the surface-modified hollow glass microspheres in the core layer are covalently bonded to the epoxy-anhydride crosslinking network via epoxy functional groups. In the core layer, these microspheres not only act as lightweight fillers but also as rigid stress transmission nodes. When the cylinder wall bends and vibrates, the stress is transmitted more evenly through these nodes and acts on the flexible polyurethane segments, improving the conformational adjustment of the polyurethane segments and the energy dissipation efficiency of intramolecular friction. While Comparative Example 2's core layer contains a higher proportion of polyurethane segments (due to the absence of microspheres occupying the volume), it lacks the rigid nodes to uniformly control the stress field, resulting in reduced participation and damping efficiency of the polyurethane segments, leading to a longer vibration decay time. Comparative Example 5, being solid carbon fiber, has very low damping, the longest decay time, and a thin sound.
[0099] The vibration decay time of Comparative Example 3 was 0.36 seconds. This is because the nano-rough structure and epoxy functional groups on the surface of the modified hollow glass microspheres formed a strong interfacial chemical bond and mechanical interlock with the polyurethane matrix, which allowed the vibration energy to be efficiently dissipated through interfacial friction and chain segment motion. The vibration decay time of Comparative Example 4 was 0.35 seconds, which was slightly shorter than that of Comparative Example 3. However, this was because the unmodified smooth microspheres had a weaker bond with the matrix interface, and were prone to interfacial slippage and debonding under alternating stress. This repeated micro-slippage process also consumed some vibration energy. At the same time, the presence of the basic resin system provided rigid support, making the overall damping effect close to that of Comparative Example 3.
[0100] Table 1 Analysis of Test Results Example 1 5H No cracks, no delamination Example 2 5H No cracks, no delamination Example 3 5H No cracks, no delamination Example 4 6H No cracks, no delamination Comparative Example 1 3H No cracks, no delamination Comparative Example 2 4H Local micro-depression Comparative Example 3 4H Partial delamination between core layer and panel Comparative Example 4 5H Microsphere detachment traces are visible within the core layer. Comparative Example 5 3H Increased surface micro-scratches The test results of interlaminar shear strength are as follows: Figure 4 As shown, Example 4 achieved an interlaminar shear strength of 19.3 MPa, while Comparative Example 3 only achieved 12.4 MPa. In Comparative Example 3, no base resin system was added to the core layer, and the hydroxyl-terminated polyurethane prepolymer could not be fully cross-linked. The bond between the prepolymer and the upper and lower carbon fiber reinforcing layers was weak, formed only by a small amount of reaction at the interface, resulting in localized delamination after thermal cycling tests. In the examples, after adding the base resin system to the core layer, the terminal hydroxyl groups of the polyurethane prepolymer co-crosslinked with the epoxy-anhydride network, forming a continuous interpenetrating structure, greatly improving the interlaminar bonding strength. Comparative Example 4 had an interlaminar shear strength of 15.5 MPa. It used unmodified hollow glass microspheres, whose surface lacked chemical bonding sites, resulting in weak bonding with the resin matrix. Under external force, the microspheres easily detached, leading to a decrease in shear strength and damage within the core layer. Comparative Example 5, a single-layer solid carbon fiber epoxy bathtub, did not undergo interlaminar shear strength testing.
[0101] Table 1 shows the post-heat and wet cycling conditions. No cracks or delamination were observed in Examples 1 and 5, while delamination occurred in Comparative Example 3, localized micro-indentations were observed in Comparative Example 2, and traces of microsphere detachment were observed in Comparative Example 4. This demonstrates the importance of the overall chemical bonding structure between layers and the role of modified microspheres in maintaining the integrity of the core layer.
[0102] Test results show that this invention improves surface hardness and gloss by introducing self-made pearlescent filler into the transparent gel coat layer, and constructs a co-crosslinked interpenetrating network in the core layer with modified hollow glass microspheres, hydroxyl-terminated polyurethane prepolymer, and basic resin system, achieving lightweight, vibration reduction and noise reduction, scratch resistance and pearlescent decorative effect.
[0103] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A lightweight carbon fiber bathtub, characterized in that, The bathtub comprises, from the outside in, a transparent gel coat layer, an outer surface reinforcement layer, a microsphere-filled core layer, and an inner structural layer; The transparent gel coat layer is formed by coating and curing a base resin system with added pearlescent fillers. The outer surface reinforcement layer is formed by curing carbon fiber twill fabric impregnated with the base resin system; The microsphere-filled core layer is formed by mixing hydroxyl-terminated polyurethane prepolymer, a base resin system and modified hollow glass microspheres, then coating and curing the mixture. The modified hollow glass microspheres are hollow glass microspheres whose surfaces have been treated with nano-silica deposition and epoxy-functionalized silane coupling agent. The inner structural layer is formed by curing carbon fiber twill fabric impregnated with the base resin system.
2. A method for preparing a lightweight carbon fiber bathtub according to claim 1, characterized in that, Includes the following steps: After applying a release agent to the working surface of the bathtub mold, a layer of transparent gel coat resin system is applied. The transparent gel coat resin system includes a base resin system and pearlescent filler, with a thickness of 0.12 mm to 0.25 mm, and gels at room temperature until it is no longer sticky. Two layers of carbon fiber twill fabric are laid on the gel coat layer, and the base resin system is brushed or poured onto the fabric to impregnate it, forming an outer surface reinforcement layer. A core layer slurry is coated onto the outer surface reinforcement layer. The core layer slurry is made of a mixture of hydroxyl-terminated polyurethane prepolymer, a base resin system, and modified hollow glass microspheres. The coating thickness is 0.8 mm to 2.5 mm. Three layers of carbon fiber twill fabric are laid on the core layer slurry. The base resin system is brushed or poured onto the fabric to impregnate it, forming an inner structural layer. Then, cover the bathtub with a release film, a breathable felt, and a vacuum bag film in sequence. After sealing, vacuum solidify the bathtub and let it cool in the oven to below 55°C before demolding. Finally, polish the surface to obtain the finished bathtub.
3. The method for preparing a lightweight carbon fiber bathtub according to claim 2, characterized in that, The specific steps of the vacuum curing are as follows: evacuate to below -0.090 MPa, raise the temperature from room temperature to 80°C to 90°C at a rate of 0.8°C / min to 1.5°C / min, hold for 1.5 hours to 2 hours, continue to raise the temperature to 120°C to 140°C, and hold for 2.5 hours to 3.5 hours.
4. The method for preparing a lightweight carbon fiber bathtub according to claim 2, characterized in that, The basic resin system comprises a uniform mixture of bisphenol A type epoxy resin, methyl hexahydrophthalic anhydride, and 2,4,6-tris(dimethylaminomethyl)phenol, wherein the mass ratio of bisphenol A type epoxy resin to methyl hexahydrophthalic anhydride is 100:82 to 100:88, and the amount of 2,4,6-tris(dimethylaminomethyl)phenol added is 0.5% to 1.5% of the mass of bisphenol A type epoxy resin.
5. The method for preparing a lightweight carbon fiber bathtub according to claim 2, characterized in that, The amount of pearlescent filler added is 4% to 12% of the mass of bisphenol A epoxy resin in the base resin system.
6. The method for preparing a lightweight carbon fiber bathtub according to claim 5, characterized in that, The preparation method of the pearlescent filler includes the following steps: dispersing flaky sericite powder with an aspect ratio of not less than 40 and a particle size of 5 to 25 micrometers in water to prepare an aqueous suspension with a mass concentration of 15% to 25%; adding aluminum chloride solution to the aqueous suspension to make the aluminum ion concentration 0.10 mol / L to 0.25 mol / L. Ammonia solution was added dropwise at 60°C to 80°C with stirring to adjust the pH to 5.5 to 6.
5. The reaction was continued for 1 to 2 hours with stirring, followed by filtration and washing. The mixture was then calcined at 800°C to 950°C for 1.5 to 3 hours to obtain alumina-coated mica composite powder. The alumina-coated mica composite powder was ultrasonically dispersed in toluene, and a mixed silane with a mass ratio of methyltriethoxysilane to phenyltrimethoxysilane of 2:1 to 3:1 was added. The total amount of mixed silane added was 5% to 12% of the mass of the alumina-coated mica composite powder. The mixture was reacted at 75°C to 90°C under a nitrogen atmosphere for 6 to 9 hours, followed by washing and drying to obtain pearlescent filler.
7. The method for preparing a lightweight carbon fiber bathtub according to claim 2, characterized in that, The preparation of the core layer slurry includes the following steps: adding modified hollow glass microspheres to a hydroxyl-terminated polyurethane prepolymer, then adding a basic resin system, stirring and mixing evenly and degassing to obtain the core layer slurry; the amount of the basic resin system added is 30% to 80% of the mass of the hydroxyl-terminated polyurethane prepolymer; The modified hollow glass microspheres are added at an amount of 20% to 48% of the mass of the hydroxyl-terminated polyurethane prepolymer; the mixing is carried out in a planetary stirrer at a speed of 200 rpm to 500 rpm for a time of 20 to 40 minutes; the degassing is carried out under a vacuum of -0.085 MPa for a time of 10 to 20 minutes.
8. The method for preparing a lightweight carbon fiber bathtub according to claim 7, characterized in that, The preparation method of the modified hollow glass microspheres includes the following steps: preparing microspheres with a particle size distribution of 15 to 45 micrometers and a true density of 0.15 g / cm³. 3 Up to 0.30 g / cm 3 Hollow glass microspheres were immersed in a 4% to 8% sodium hydroxide aqueous solution at 35°C to 50°C for 20 to 40 minutes, then washed and dried. Next, they were immersed in an ethanol-water solution containing tetraethyl orthosilicate, wherein the volume ratio of ethanol to water was 95:5, and the concentration of tetraethyl orthosilicate was 0.05 mol / L to 0.12 mol / L. The pH was adjusted to 9 to 10 with ammonia, and the mixture was stirred at 35°C to 45°C for 4 to 8 hours. The tetraethyl orthosilicate hydrolyzed and condensed to form nano-silica, which was deposited on the surface of the hollow glass microspheres, forming a layer with a thickness of 20 nm to 80 nm. A nano-silica deposition layer of nm was obtained, filtered, and dried at 110°C to 130°C for 30 to 60 minutes. Then, it was immersed in an ethanol-water solution containing γ-glycidoxypropyltrimethoxysilane, wherein the volume ratio of ethanol to water was 95:5, and the mass concentration of γ-glycidoxypropyltrimethoxysilane was 1.0% to 2.5%, and soaked at room temperature for 40 to 80 minutes. After removal, it was heat-treated at 90°C to 110°C for 1.5 to 3 hours to obtain modified hollow glass microspheres.
9. The method for preparing a lightweight carbon fiber bathtub according to claim 7, characterized in that, The preparation method of the hydroxyl-terminated polyurethane prepolymer includes the following steps: Poly(1,4-butanediol adipate) diol with a number-average molecular weight of 1800 to 3200 and isophorone diisocyanate are added to a reactor at a molar ratio of NCO to OH of 0.65:1 to 0.85:1; dibutyltin dilaurate is added as a catalyst, the amount of which is 0.01% to 0.03% of the total material mass; the poly(1,4-butanediol adipate) diol is vacuum dehydrated at 100°C to 120°C until the water content is below 0.05% before being added; the reaction is carried out under nitrogen protection; the reaction is carried out at 70°C to 80°C for 1.5 to 2.5 hours; the NCO content is monitored until the detection value reaches zero, and the reaction is terminated to obtain a hydroxyl-terminated polyurethane prepolymer with a hydroxyl value of 35 mgKOH / g to 65 mgKOH / g.
10. The method for preparing a lightweight carbon fiber bathtub according to claim 2, characterized in that, The carbon fiber twill fabric is a 3K carbon fiber twill fabric with a basis weight of 200 gsm to 240 gsm and a single layer thickness of 0.25 mm to 0.35 mm.